Tracking Response Dynamics of Sequential Working Memory in Patients With Mild Parkinson’s Disease - Zhang, Guanyu; Ma, Jinghong; Chan, Piu; Ye, Zheng (Frontiers in Psychology, 2021)
The ability to sequence thoughts and actions is impaired in Parkinson’s disease (PD). In PD, a distinct error pattern has been found in the offline performance of sequential working memory. This study examined how PD’s performance of sequential working memory unfolds over time using mouse tracking techniques. Nondemented patients with mild PD (N=40) and healthy controls (N=40) completed a computerized digit ordering task with a computer mouse. We measured response dynamics in terms of the initiation time, ordering time, movement time, and area under the movement trajectory curve. This approach allowed us to distinguish between the cognitive processes related to sequence processing before the actual movement (initiation time and ordering time) and the execution processes of the actual movement (movement time and area under the curve). PD patients showed longer initiation times, longer movement times, and more constrained movement trajectories than healthy controls. The initiation time and ordering time negatively correlated with the daily exposure to levodopa and D2/3 receptor agonists, respectively. The movement time positively correlated with the severity of motor symptoms. We demonstrated an altered temporal profile of sequential working memory in PD. Stimulating D1 and D2/3 receptors might speed up the maintenance and manipulation of sequences, respectively.